Developing paleogeographic heritage concepts and ideas through the Upper Jurassic record of the Salgado and Consolação geosites (Lusitanian Basin, Portugal) - Henriques, M. H. (2022)
The Salgado and Consolação geosites are located on the Portuguese coast of the West Iberian Margin and represent two Upper Jurassic reference sections of the Amaral Formation interpreted as a barrier-lagoon depositional environment within a mixed carbonate platform context. Outcrops exposure and access conditions allow the detailed study of the succession, as well as its use as a geotourism target, and as a particular relevant geoeducation resource. But, in addition, these geosites, due to their geodiversity, can also serve as particularly interesting case study in the deepening of concepts and ideas that are being building geoconservation as an emerging geological science. The objective of the present work is: to discuss the type of geoheritage that Salgado and Consolação geosites represent; to identify and describe the geoheritage contents of the two geosites, as well as to assess, from a qualitative point of view, their values; to use the geoheritage contents of the two geosites to support an educational intervention including fieldtrips; and to frame the concept of palaeogeographic heritage within the broad meaning assigned to geological heritage.